FACTORS RELATED SUCCESFUL SKIN TO SKIN ON FIRST HOUR AFTER BIRTH - Suhaid, Dewi Novitasari; Kadarsih, Mitra; Dini, Kusuma (HEARTY, 2024)
Skin-to-skin contact (SSC) is a crucial step in early breastfeeding initiation, contributing to the success of exclusive breastfeeding and neonatal adaptation. However, its implementation still faces various challenges. This study aims to analyze factors associated with the timely implementation of SSC within the first hour after birth. A retrospective observational design was employed using medical record data from a hospital in Jakarta between January and December 2022. A total of 56 mothers were selected through simple random sampling. Data analysis was conducted using the chi-square test to examine the relationship between delivery method, maternal age, and education level with SSC implementation. The results showed significant associations between SSC and delivery method (p = 0.006), maternal age (p = 0.034), and education level (p = 0.008). Mothers who underwent cesarean section were more likely to receive SSC within the first hour compared to those with vaginal delivery. Additionally, mothers within the non-risk age category and those with a basic education level were more likely to implement SSC on time. In conclusion, SSC implementation is influenced by maternal and delivery-related factors, emphasizing the need for increased awareness among healthcare professionals to promote optimal SSC practices.